First report on the leafhopper genus Balera Young (Hemiptera, Cicadellidae, Typhlocybinae, Alebrini) from Argentina, and description of a new species - Catalano, María Inés (2013)
The genus Balera Young is reported for first time to Argentina and a new species is described, Balera floripara sp. n. Detailed morphological descriptions and illustrations of the new species and a key to males of known species are provided. Habralebra amoena is also recorded for the first time from Argentina.